2013
DOI: 10.1373/clinchem.2012.195560
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Urinary Prostate Cancer Antigen 3 and TMPRSS2:ERG Gene Fusion with the Serum [−2]Proprostate-Specific Antigen–Based Prostate Health Index for Detection of Prostate Cancer

Abstract: BACKGROUND We compared urinary prostate cancer antigen 3 (PCA3), transmembrane protease, serine 2 (TMPRSS2):v-ets erythroblastosis virus E26 oncogene homolog (avian) (ERG) gene fusion (T2:ERG), and the serum [−2]proprostate-specific antigen ([−2]proPSA)-based prostate health index (Phi) for predicting biopsy outcome. METHODS Serum samples and first-catch urine samples were collected after digital rectal examination (DRE) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
70
2
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 45 publications
1
70
2
5
Order By: Relevance
“…6,23 To date 2 studies have reported on head-to-head comparisons between PCA3 and PHI to establish which test has the highest accuracy in predicting prostate cancer with RB. 7,8 In the first study the performance of the 2 biomarkers was compared in a cohort of 246 patients undergoing initial or repeat biopsy. 7 In the RB cohort the PCA3 results were more discriminating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,23 To date 2 studies have reported on head-to-head comparisons between PCA3 and PHI to establish which test has the highest accuracy in predicting prostate cancer with RB. 7,8 In the first study the performance of the 2 biomarkers was compared in a cohort of 246 patients undergoing initial or repeat biopsy. 7 In the RB cohort the PCA3 results were more discriminating.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In the first study the performance of the 2 biomarkers was compared in a cohort of 246 patients undergoing initial or repeat biopsy. 7 In the RB cohort the PCA3 results were more discriminating. In the second study Scattoni et al evaluated the results of the 2 biomarkers in 95 patients who underwent RB.…”
Section: Discussionmentioning
confidence: 99%
“…While prostate-specific antigen (PSA) remains the basic parameter, the additional value of the two 2012 FDA-approved biomarkers prostate health index (PHI) in serum and prostate cancer gene 3 (PCA3) in urine has been confirmed numerous times [1]. The detection of TMPRSS2-ERG gene fusions in the tissue of approximately 50% of all prostate cancer patients and the subsequently developed urinary assay [2] put hope on further diagnostic improvement that could unfortunately only be partially fulfilled [3][4][5].The senior author of this article [6] in this issue of Clinical Chemistry and Laboratory Medicine played the key role in detecting PCA3 and developing urinary assays for PCA3 and TMPRSS2-ERG [7]. And this group is now the first that compared both markers in whole urine, urinary sediment and exosomes.…”
mentioning
confidence: 99%
“…While prostate-specific antigen (PSA) remains the basic parameter, the additional value of the two 2012 FDA-approved biomarkers prostate health index (PHI) in serum and prostate cancer gene 3 (PCA3) in urine has been confirmed numerous times [1]. The detection of TMPRSS2-ERG gene fusions in the tissue of approximately 50% of all prostate cancer patients and the subsequently developed urinary assay [2] put hope on further diagnostic improvement that could unfortunately only be partially fulfilled [3][4][5].…”
mentioning
confidence: 99%
“…Chwatko et al [11] did not incorporate the already mentioned new urinary biomarkers PCA3 and TMPRSS2:ERG in the study. In recent studies, especially PCA3 has been proven to be superior to PSA and percent free PSA [24,25]. Thus, a comparison of the clinical validity of thiosulfate with PCA3 and TMPRSS2:ERG in a cohort with similar PSA concentrations below 10 µg/L or at least < 20 µg/L would be necessary.…”
mentioning
confidence: 99%